Cep55 promotes cytokinesis of neural progenitors but is dispensable for most mammalian cell divisions - Antonio Tedeschi (Nature Portfolio, 2020)
In mammalian cell lines, Cep55 protein recruits the endosomal sorting complex required for transport (ESCRT) and promotes the completion of cell division. Here, the authors show that Cep55-knockout mice are viable and primary fibroblasts cultured in vitro divide in a Cep55 and ESCRT-independent way.